Investigation of a Fe–N–C catalyst for sulfur dioxide electrooxidation. Issue 83 (23rd August 2016) - Zhao, Qing; Hou, Ming; Jiang, Shangfeng; Wang, Shengli; Ai, Jun; Zheng, Limin; Shao, Zhigang
Abstract : A non-precious Fe–N–C catalyst is developed with the high SO2 electrooxidation performance. Abstract : A Fe–N–C catalyst, synthesized with porous carbon BP2000, the nitrogen source imidazole and iron source FeCl3, is developed for SO2 electrooxidation through a series of thermal and pyrolytic disposing processes. The electrochemical measurements of linear sweep voltammograms (LSV) and cyclic voltammograms (CV) are applied to investigate the SO2 oxidation performance of the catalyst. The results show that the half-wave oxidation potential of Fe–N–C is 283.8 mV lower than that of BP2000 meanwhile the onset oxidation potential reduces 58 mV as well, implying there is a highly improved SO2 oxidation performance of the catalyst. The structural and physical characteristics of the Fe–N–C catalyst are examined by the methods of TEM, XPS, XRD and Raman spectroscopy. The characterization proves the formation of graphitic carbon, iron carbides, single-layer graphene and defects as well as the existence of FeN/Fe2 N, pyridinic N and Fe–N components on the prepared Fe–N–C catalyst, which are supposed to have significant effects on the SO2 electrooxidation performance.